PERKEMBANGAN PERSONAL SOSIAL ANAK PRASEKOLAH LEBIH BAIK SAAT TINGGAL BERSAMA ORANG TUA - Setiawan, Arief; Nur Azizah, Fajriati (Jurnal Media Ilmu Kesehatan, 2013)
Background:Preschool children personal social development will continuously changes, systemic, andprogressive that is a reflection of relating behaviour to the ability of independent, socialize, and interactwith social environment in children aged 1?6 years (preschool) where the child lived. Parents have amain role for preschool-aged children in development  process, but in fact not all children can stay withtheir parents, because things various. Children's workhouses which has the task of providing guidanceand services for fatherless, strays, orphaned and abandoned underprivileged. Children that living inorphanages are get less appropriate likely attention required, children in orphanages have physical andmental problems, including social problems. Objective:To know the difference of preschool children personal social development have living theirparents together with living in an orphanage. Method:This is descriptive analytical research, with observational research methods, which use aquantitative cross sectional approach, research instrument using Denver Development Screening Test IIwith normal, suspect, and untestable interpretation. The sample in this research is overall of populationwhich totaled 39 childrens living parent together and 19 chidrens living in an orphanage . The test used anon parametric Mann-Whitney test to check the difference meaning, with a level significance of p<0,05. Result:There is difference of preschool children personal social development have living their parentstogether with living in an orphanage. with p value 0,018 (p<0.05). Normal category children living parentstogether 89,7%, suspect 7,7%, and untestable 2,6%. While normal category children living in orphanages63,1%, suspect 31.6%, and untestable 5,3%. Conclusion:There is difference of preschool children personal social development have living theirparents together with living in an orphanage. Where prescool children personal social development haveliving parents together is better than living in an orphanage. Keywords: Preschool, personal social development, parenting, orphanage.